Объяснение:
а) По условию возьмем х=2у (у вдвое меньше х)
Тогда: 6*2у-4у=17
12у-4у=17
8y=17
y=
x=2y=2*
Первая пара: х=4 у=
б) По условию возьмем у=2х (х вдвое меньше у)
Тогда: 6х-4*2х=17
6х-8х=17
-2х=17
х=
y=2x=2*(
Вторая пара: х= у=
Объяснение:
а) По условию возьмем х=2у (у вдвое меньше х)
Тогда: 6*2у-4у=17
12у-4у=17
8y=17
y=![\frac{17}{8} =2\frac{1}{8}](/tpl/images/1207/1803/15879.png)
x=2y=2*![\frac{17}{8} =\frac{17}{4} =4\frac{1}{4}](/tpl/images/1207/1803/9f947.png)
Первая пара: х=4
у=![2\frac{1}{8}](/tpl/images/1207/1803/b3c12.png)
б) По условию возьмем у=2х (х вдвое меньше у)
Тогда: 6х-4*2х=17
6х-8х=17
-2х=17
х=![-\frac{17}{2} =-8\frac{1}{2}](/tpl/images/1207/1803/571ff.png)
y=2x=2*(![-\frac{17}{2}) =-17](/tpl/images/1207/1803/38e2e.png)
Вторая пара: х=
у=![-17](/tpl/images/1207/1803/439fd.png)